Produção de cimento:: Impactos Ã saúde e ao meio ambiente (Sustainability in Debate, 2012)
This article aims at showing the production process of cement identifying its impacts on humanhealth, from the extraction of raw material, which generates degradation and contamination of thewater and soil, to the emission of particulate matter, which causes respiratory tract diseases. In theFederal District, in the region of Fercal in Sobradinho, the existence of two large factories generatesimpacts on the health of nearby communities. In the Community Queima Lençol, located near one ofthese factories, pollution generated by the emission of particulate matter arising from the manufactureof cement, has caused serious respiratory problems in local people.